If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + 2y = 6y + 6 Combine like terms: 5y + 2y = 7y 7y = 6y + 6 Reorder the terms: 7y = 6 + 6y Solving 7y = 6 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 7y + -6y = 6 + 6y + -6y Combine like terms: 7y + -6y = 1y 1y = 6 + 6y + -6y Combine like terms: 6y + -6y = 0 1y = 6 + 0 1y = 6 Divide each side by '1'. y = 6 Simplifying y = 6
| 3x^2-2x+8=0 | | x^2+26x-0.36=0 | | 8y-13y= | | -12=8y-4 | | x^2+26x-1=0 | | 5x^6-8x^2=0 | | 25x^4-34x^2+9=0 | | -7x+9=3 | | cx-e=fx+g | | 6(x-2)=5x-7 | | -5-8n=-6 | | 0.4(2x-3)=0.2x | | -9+4m=-3 | | t^2-64=0 | | 67-2x=16x+17 | | x^2+2-15=0 | | 6-8x=206-43x | | 16x^4-x^2=0 | | 91-3x=2x+21 | | 3-12r=-5 | | -49-2x=11-8x | | w+7*5+2= | | M^2-3mn-2n^2= | | 3x+5=-75-7x | | 117-6x=10x+21 | | a^2-10ab-24b^2= | | w^2*.5w-288=0 | | w^2+.5w-288=0 | | 7+5x=39+x | | w(w*.5)-288=0 | | 3x-5=12x-104 | | 5x+32=15x-88 |